Common framework mutations impact antibody interfacial dynamics and flexibility - Rhodes, Emily R.; Faris, Jonathan G.; Petersen, Brian M.; Sprenger, Kayla G. (Frontiers in Immunology, 2023)
With the flood of engineered antibodies, there is a heightened need to elucidate the structural features of antibodies that contribute to specificity, stability, and breadth. While antibody flexibility and interface angle have begun to be explored, design rules have yet to emerge, as their impact on the metrics above remains unclear. Furthermore, the purpose of framework mutations in mature antibodies is highly convoluted. To this end, a case study utilizing molecular dynamics (MD) simulations was undertaken to determine the impact framework mutations have on the VH-VL interface. We further sought to elucidate the governing mechanisms by which changes in the VH-VL interface angle impact structural elements of mature antibodies by looking at root mean squared deviations (RMSD), VH-VL interface angle, root mean squared fluctuations (RMSF) and solvent exposed surface area (SASA). Overall, our results suggest framework mutations can significantly shift the distribution of VH-VL interface angles which leads to increased flexibility by changing which portions of the antibody have a greater solvent exposed surface area. The data presented herein highlights the need to reject the dogma of static antibody crystal structures and exemplifies the dynamic nature of these proteins in solution. Findings from this work further demonstrate the importance of framework mutations on antibody structure and lay the foundation for establishing design principles to create antibodies with increased specificity, stability, and breadth.